Industrial Relations and Unemployment Benefit Schemes in the Visegrad Countries during the COVID-19 Pandemic - Katarína Lukáčová; Lucia Kováčová; Martin Kahanec (Global Labor Organization (GLO), 2022)
The COVID-19 pandemic and the ensuing economic and technological adjustment increased the risk of unemployment, underemployment and skills mismatch across Europe. These increased risks highlighted the importance of national unemployment benefit schemes for income security. This article examines the role of industrial relations in shaping unemployment benefit regimes in the Visegrad countries during the COVID-19 pandemic. We adopted an actor-oriented approach based on desk research and 12 semi-structured interviews with the representatives of trade unions and employers in all the Visegrad countries. Our research showed that the capacities of the trade unions and employers' associations to shape the unemployment benefit regimes were rather limited. State control over social policy remained very strong and shaped the dynamics of industrial relations, without inclusive involvement of social partners. National governments sought to implement measures to protect employment (mainly wage subsidies), rather than to reform existing unemployment support regimes.
Keywords: 330; Unemployment benefits; short-time work; industrial relations; Visegrad countries; Central and Eastern Europe; COVID-19 pandemic